2020
DOI: 10.1111/sum.12661
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing phosphorus availability, soil organic carbon, maize productivity and farm profitability through biochar and organic–inorganic fertilizers in an irrigated maize agroecosystem under semi‐arid climate

Abstract: Biochar amendments offer promising potential to improve soil fertility, soil organic carbon (SOC) and crop yields; however, a limited research has explored these benefits of biochar in the arid and semi‐arid regions. This two‐year field study investigated the effects of Acacia tree biomass‐derived biochar, applied at 0 and 10 t ha‒1 rates with farmyard manure (FYM) or poultry manure (PM) and mineral phosphorus (P) fertilizer combinations (100 kg P ha‐1), on maize (Zea mays L.) productivity, P use efficiency (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 106 publications
1
22
0
1
Order By: Relevance
“…Similarly, larger changes in the soil properties were reported for the coarse-than fine-textured soils for equivalent biochar application rate (Omondi et al, 2016;Razzaghi et al, 2020). Enhanced soil properties, crop yield and economic benefits (Arif et al, 2021;Dong et al, 2021;Ye et al, 2020) were reported for the integration of biochar with other organic and/or mineral amendments compared to the sole application of biochar. The beneficial influence of biochar rises with time (Kätterer et al, 2019), and this is particularly noticeable for biochar having smaller particle sizes (Esmaeelnejad et al, 2016;Liu et al, 2017) owing to carbon interaction with soil particles as biochar ages, ease of mix, enhanced aggregate formation and greater specific surface area per unit of mass among other attributes.…”
mentioning
confidence: 81%
“…Similarly, larger changes in the soil properties were reported for the coarse-than fine-textured soils for equivalent biochar application rate (Omondi et al, 2016;Razzaghi et al, 2020). Enhanced soil properties, crop yield and economic benefits (Arif et al, 2021;Dong et al, 2021;Ye et al, 2020) were reported for the integration of biochar with other organic and/or mineral amendments compared to the sole application of biochar. The beneficial influence of biochar rises with time (Kätterer et al, 2019), and this is particularly noticeable for biochar having smaller particle sizes (Esmaeelnejad et al, 2016;Liu et al, 2017) owing to carbon interaction with soil particles as biochar ages, ease of mix, enhanced aggregate formation and greater specific surface area per unit of mass among other attributes.…”
mentioning
confidence: 81%
“…Its impact on soil amendment includes increased soil quality and plant growth with enhancement in crop yield. The response and behavior of biochar can be substantially influenced by its manufacturing process, soil conditions and types where applied, and as well as the kind of crop to be grown [10,11]. In keeping with the importance of biochar, many researchers have studied the adaptability of biochar for the improvement of soil and environmental health.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is known to possess well‐developed porous structures (Kwiatkowski & Kalderis, 2020; Leng et al, 2021), abundant functional groups (Ahmad et al, 2014; Wang, Ok, et al, 2020), various inorganic nutrients (Dai et al, 2020; Smider & Singh, 2014) and high carbon stability (Li et al, 2014; Spokas, 2010). Therefore, biochar can be used for various purposes, including soil fertility improvement (Arif et al, 2020; El‐Naggar et al, 2019), contaminant immobilization (Palansooriya et al, 2020; Shen et al, 2018; Wang et al, 2020), wastewater treatment (Shaheen et al, 2019; Thompson et al, 2016; Xiang et al, 2020), flue gas purification (Shan et al, 2019; Shi et al, 2020) and in situ carbon storage (Han Weng et al, 2017; Hardy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%